Prisoners' Labour Market History and Aspirations: A Focus on Western Australia - Anh Tram Le
This paper examines the employability and labour market aspirations of prisoners. The results suggest that repeat prisoners are less likely to be employed than nonrepeat prisoners. However, a large proportion of the employment differential between repeat and non-repeat prisoners is due to differences in coefficients. There is no evidence to suggest that the frequency of incarceration affects individual characteristics which may limit prisoners’ labour market aspirations after their release from prison.